Thermogravimetric investigations of nasal gel with diltiazem - L. K. Kuchina; V. V. Gladyshev; I. A. Puchalskaya (Zaporozhye State Medical University, 2015)
Aim. To conduct the thermogravimetric investigations of nasal gel with diltiazem. Methods and results. Using alternative ways of diltiazem absorption, in particular, nasal, will allow to improve its bioavailability and efficiency. Derivatografic investigations of the active substances and excipients have been carried out for the purpose of the thermal treatment effects of nasal gel study. It has been revealed that developed diltiazem nasal dosage form on the base of methylcellulose glycerogel is mechanical mixture of the active substances and excipients because its ingredients don't interact. Conclusion. Preparation of the diltiazem nasal gel 5% by temperature under 90ºС doesn't lead to destruction of the components of the present dosage form.